2018
DOI: 10.1002/jcb.27192
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory role of curcumin on platelet functions

Abstract: Curcumin, the main ingredient of Curcuma longa L., has been used as a spice and as a herbal medicine with different therapeutic characteristics for centuries in Asian countries. This phytochemical has been shown to possess beneficial antiplatelet activity that has introduced it as a promising candidate for the treatment of thromboembolism, atherothrombosis, and inflammatory diseases. Platelet dysfunction under different circumstances may lead to cardiovascular disease, and curcumin has been shown to have benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 78 publications
0
23
0
Order By: Relevance
“…However, approved drugs for the treatment of cancer are usually limited by potential undesirable side effects such as hepatotoxicity, nephrotoxicity, ototoxicity, reduction in platelet counts, and myelosuppression . Curcumin, a natural polyphenolic compound and the principal coloring agent found in the rhizomes of Curcuma longa (Zingiberaceae), has several health benefits, including antioxidant , anti‐inflammatory , immunomodulatory , antiarthritic , antithrombotic , pulmonoprotective , lipid‐modifying , neuroprotective , anticancer , antidiabetic, and hepatoprotective properties. Numerous reports have indicated that curcumin is quite safe and nontoxic to humans up to doses of 12 g/day .…”
Section: Introductionmentioning
confidence: 99%
“…However, approved drugs for the treatment of cancer are usually limited by potential undesirable side effects such as hepatotoxicity, nephrotoxicity, ototoxicity, reduction in platelet counts, and myelosuppression . Curcumin, a natural polyphenolic compound and the principal coloring agent found in the rhizomes of Curcuma longa (Zingiberaceae), has several health benefits, including antioxidant , anti‐inflammatory , immunomodulatory , antiarthritic , antithrombotic , pulmonoprotective , lipid‐modifying , neuroprotective , anticancer , antidiabetic, and hepatoprotective properties. Numerous reports have indicated that curcumin is quite safe and nontoxic to humans up to doses of 12 g/day .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, curcumin supplementation causes increased bile formation and demonstrates cholekinetic effects [57,58]. Moreover, curcumin presents antiplatelet, anticoagulation, and fibrinolysis activities [59,60]. In addition, curcumin supplementation increases insulin sensitivity and subsequently leads to lower blood glucose levels among diabetic patients who were taking diabetes medications [61,62].…”
Section: Common Adverse Effects Between Covid-19 and Curcuminmentioning
confidence: 99%
“…Curcumin is a naturally occurring nutraceutical compound with diverse pharmacological impacts such as antioxidant, anti-inflammatory, anti-diabetic and anti-tumor [118,119,120,121]. It appears that curcumin is capable of targeting different signaling pathways in stimulation of its anti-tumor activity and JAK-STAT pathway is one of them [122,123,124,125].…”
Section: Stats Inhibitorsmentioning
confidence: 99%